Evaluating the change in immunoglobulin G and accuracy of assessing transfer of passive immunity during the first 7 days of age in Holstein dairy calves fed colostrum replacer - H.M. Goetz; M.A. Steele; K. Nott; H.R. McCarthy; A.J. Lopez; M.C. Cantor; D.L. Renaud (Journal of Dairy Science)
ABSTRACT: Accurate diagnosis of failure of transfer of passive immunity is an important component for dairy herd management goals and involves measurement of serum IgG in young calves. However, it is not well understood how IgG concentration changes over the first week of life. The primary objective of this cohort study was to evaluate how blood serum IgG concentrations change in dairy calves fed colostrum replacer during the first 7 d of life. This cohort study combined data collected from 4 different studies that evaluated different colostrum management strategies. Daily blood samples and health scores were collected during the first 7 d of life in male and female Holstein calves between May 2021 to August 2023 (n = 365). Serum was separated and analyzed in a commercial laboratory via radial immunodiffusion to determine IgG concentrations. Results were further categorized based on IgG concentration into “excellent” (25.0 g/L), “good” (18.0–24.9 g/L), “fair” (10.0–17.9 g/L), and “poor” (<10.0 g/L) categories. Mixed linear regression models were used to determine the effect of day of sampling relative to birth and d-1 transfer of passive immunity (TPI) classification on change in IgG concentration, whereas mixed ordinal logistic regression models were built to evaluate the odds of being in a different TPI category on d 2 through 7 compared with d 1 of life. A random effect for calf within trial was included in all models. The median (range) IgG concentration on d 1 (i.e., between 24 and 48 h of age) was 22.3 g/L (8.1–43.1 g/L) and decreased to a median of 11.7 g/L (4.8–60.1 g/L) on d 7. When IgG values were categorized, there was an increase in calves with poor TPI (3.3% of calves on d 1 to 33.5% of calves on d 7) across the first 7 d of life. In the mixed linear regression models, all days were statistically different from IgG measured on d 1. Specifically, IgG progressively decreased each day relative to d 1 until d 6. In the mixed effects ordinal logistic regression model, the odds of being categorized into a different passive immunity category on d 2 relative to d 1 based on IgG was 0.43 (95% CI = 0.29–0.63), which continued to decline on d 3 through 7. This study shows that calf age at the time of assessing TPI affects interpretation of serum IgG in calves fed colostrum replacer. Thus, serum IgG should be assessed between 24 and 48 h of age when feasible, to consistently evaluate passive immunity status when serum IgG is highest in colostrum replacer-fed calves.